Sustaining innovation: Creativity among employees of small and medium-sized enterprises and students in higher education institutions in Brunei Darussalam - Solomon Uche Obiwulu; Esa M. Yunus; Fahmi Ibrahim; Abu Samah Zuruzi (Journal of Open Innovation: Technology, Market, and Complexity, 2019)
This paper compares creativity experiences and perceptions among employees of small and medium-sized enterprises (SME) and students in higher education institutions (HEI) in Brunei Darussalam. The study was conducted through interactions and surveys to assess (i) understanding and practice of creative tools and techniques; (ii) creativity performance in teams and individuals and (iii) perception of creativity among 39 employees in SME and 68 students from HEI. Statistical analysis was carried out using Pearson's chi-square test for goodness of fit and Cramer's V test to estimate strength tests for correlation. The findings indicate a majority in both groups have not received prior instruction in creativity and that employees of SMEs have less interest in receiving creative instructions. There is consensus among both groups that group work will result in greater creative performance. Ambiguity of customer needs or requirement was a factor most often cited to impede creative performance of teams in SME. Results from this study were used to make recommendations to improve practice and learning creativity in SME and HEI.
Keywords: 650; innovation; creative design; creativity education; knowledge acquisition; teamwork